Dampak KDRT terhadap Jumlah Penurunan Angka Pernikahan di KUA Medan Amplas - Wulan Febriyanti; Aminah Rambe; M. Zulfri Hakim (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Marriage is a marriage contract between a man and a woman in accordance with legal provisions and religious teachings. Some comments suggest holding a reception after the marriage contract is held so that it becomes an announcement that the bride and groom are legally obedient religion and state. This research will discuss the decline in the number of marriages due to the rise of domestic violence in Indonesia, both at the KUA and at home, hopefully it will be useful to strengthen knowledge about proper marriage procedures, due to the many behaviors of domestic violence. As determined by the Indonesian government. This study took cases in the Medan Amplas area, to be precise in the KUA of Medan Amplas District. This study aims to analyze the increase in the number of marriages during a time when cases of domestic violence were rampant, including collecting the reasons given by some people who chose to marry during a time when domestic violence was rampant and the responses of KUA Medan Amplas officials. Keywords: Impact, domestic violence, decline, marriage